THE EFFECT OF MOBILE HEALTH ON TREATMENT EFFECTIVENESS AND COMPLIANCE IN PULMONARY TUBERCULOSIS (TB) PATIENTS: LITERATURE REVIEW - Anggia Astuti; Indra Muliani; Arista Maisyaroh; R. Endro Sulistyono (STIKes Kepanjen, 2022)
ABSTRACTIntroduction: Tuberculosis (TB) is a health problem of global concern. Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis in the lower respiratory tract. Pulmonary TB treatment for 6 months. The possibility of patients not being obedient to taking medication is very large because of the long treatment time, the large number of drugs, side effects, the patient's lack of awareness of the disease and the patient does not take the drug because he forgets. the use of reminders (mobile health) has the potential to help promote TB treatment adherence. Method: The method used in this study is a literature review. source of articles using Springerlink, PubMed and Scholar database databases.Result: The results of 9 articles assessed that the use of Mobile Health consisted of automatic sms, phone calls, and educational videos. Utilization of various types of mHealth is used according to the needs of the patient. The benefits of Mobile Health are automatic sms and telephone, namely as a reminder to take medication and schedule regular visits. Educational videos provide information about TB and the motivation of the peer group. The use of Mobile Health technology can improve TB patient compliance in treatment with medication reminder methods, regular visit schedules, education, and social support. Some of the benefits of using Mobile Health have been proven by several studies abroad.Conclusion: The use of Mobile Health technology can be an alternative to increase TB patient compliance in treatment with medication reminder methods, regular visit schedules, education, and social support and Mobile Health has a significant influence on the effectiveness and compliance of treatment in pulmonary TB patients.